Pengaruh Pembiasaan Shalat Dhuha Terhadap Karakter Siswa-Siswi SMK N 1 Abung Selatan - Hidayah, Wahyudi (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This study aims to find information whether the prevalence of dhuha prayer has an impact on the personality of students of SMK N 1 Abung Selatan. This type of research is quantitative research. The subject of this research is an apprentice teacher at SMK N 1 Abung Selatan. The samples in this study were 15 samples of TKJ 12 grade students and 15 samples of TKJ 2 grade students, so that the total sample size was 30 people. In this study the research instrument used a Likert scale questionnaire. The data analysis used is SPSS 23 to test the validity and reliability. After calculating the Pearson correlation, the rxy is 0.509. The index is 0.40-0.70, which means that there is a very strong correlation between variables X and Y. The rx1x2y rtable is 0.361, so the null hypothesis (Ho) is rejected, and the alternative hypothesis (Ha) is accepted. This means that there is a significant or moderate relationship between the habit of praying dhuha (variable X) with student personality (variable Y) SMK N 1 Abung Selatan